2013
DOI: 10.1093/annonc/mdt134
|View full text |Cite
|
Sign up to set email alerts
|

Substantial breast cancer risk reduction and potential survival benefit after bilateral mastectomy when compared with surveillance in healthy BRCA1 and BRCA2 mutation carriers: a prospective analysis

Abstract: Background: To prospectively assess the efficacy of bilateral risk-reducing mastectomy (BRRM) when compared with surveillance on breast cancer (BC) risk and mortality in healthy BRCA1 and BRCA2 mutation carriers.Patients and methods: Five hundred and seventy healthy female mutation carriers (405 BRCA1, 165 BRCA2) were selected from the institutional Family Cancer Clinic database. Eventually, 156 BRCA1 and 56 BRCA2 mutation carriers underwent BRRM. The effect of BRRM versus surveillance was estimated using Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 23 publications
5
67
0
5
Order By: Relevance
“…Based on model calculations, it is estimated that without intervention, 47% of BRCA1 mutation carriers und 29% of BRCA2 mutation carriers will die before reaching age 70, compared to 16% in the general US population [71]. In this situation, offering early detection measures for secondary prevention to high-risk women means taking on a large responsibility, especially as effective surgical prevention measures such as bilateral risk-reducing mastectomy and/or salpingo-oophorectomy are available [72,73]. Unfortunately, very few reliable data are available regarding the effectiveness of intensified surveillance in high-risk women in regards to reducing breast cancer mortality [6,22,74].…”
Section: Impact On Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on model calculations, it is estimated that without intervention, 47% of BRCA1 mutation carriers und 29% of BRCA2 mutation carriers will die before reaching age 70, compared to 16% in the general US population [71]. In this situation, offering early detection measures for secondary prevention to high-risk women means taking on a large responsibility, especially as effective surgical prevention measures such as bilateral risk-reducing mastectomy and/or salpingo-oophorectomy are available [72,73]. Unfortunately, very few reliable data are available regarding the effectiveness of intensified surveillance in high-risk women in regards to reducing breast cancer mortality [6,22,74].…”
Section: Impact On Mortalitymentioning
confidence: 99%
“…However, intensified surveillance appears to be somewhat less effective in BRCA1 mutation carriers [6], in whom more advanced stage cancers, symptomatic interval cancers as well as breast cancer deaths have been observed despite regular screening with MRI in several of the high-risk surveillance observational studies [61,66,73,78,79]. In the analysis of Heijnsdijk et al [61], which combined data from the Dutch, Canadian and UK high-risk screening trials, the share of T1c and T2+ tumors was 29% and 22%, respectively, for BRCA1 mutation carriers, compared to 16% and 4% for BRCA2 mutation carriers.…”
Section: Impact On Mortalitymentioning
confidence: 99%
“…Several studies have shown both mastectomies and oophorectomies to be effective in cancer risk reduction, though the relative benefit of mastectomy compared to less invasive methods (i.e. intensive screening, chemoprevention) remains uncertain and long-term survival benefits need confirmation [11,12,13]. As these elective surgeries come with significant risk, financial cost, and personal sacrifice, they are not universally recommended by the United States Preventive Services Task Force (USPSTF) or the National Comprehensive Cancer Network.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos prospectivos que apresentam risco relativo para neoplasias malignas de mama e ovário após a realização de salpingo-ooforectomia redutora de risco (45,(127)(128)(129)(130) . .. Estudos prospectivos que apresentam risco relativo para câncer de mama após a realização de mastectomia bilateral profilática (45,(131)(132)(133) . (31,32,(136)(137)(138) .…”
Section: Lista De Figurasunclassified
“…Estudos prospectivos que apresentam risco relativo para câncer de mama após a realização de mastectomia bilateral profilática (45,(131)(132)(133) . (17,43,44,131,(134)(135)(136) .…”
Section: Estudo Participantesunclassified